USE OF SLAG MATERIALS IN ROAD CONSTRUCTION - Krayushkina, K.; Khimerik, T.; Pershakov, V.; Bieliatynskyi, A. (Proceedings of National Aviation University (archive), 2019)
In the design of the pavement layers of the base have the greatest thickness. Therefore, their construction is associated with a high consumption of building materials. At the same time, the base layers work in more favorable conditions when compared with coatings, which makes it possible to widely use local materials and industrial waste for their construction. The feasibility of their use is justified by technical and economic calculations, taking into account the possible reduction of the service life of the pavement as a result of the rejection of the use of standard imported materials. One of the most widely known types of waste used in road construction is slags from ferrous and non-ferrous metallurgy and phosphorus production. Their disposal is an important source of high-quality materials for road construction. Slag is a valuable raw material for the preparation of non-metallic materials and mineral binders. Active slags partially replace traditional binders (cement, lime) during the construction of road foundations and coatings. Long-term experience of road organizations shows that the cost of slag road-building materials is two times lower than the cost of similar products from natural rocks.